Analisis Perilaku Biaya Pada Industri Rumah Tangga Tempe Akibat Adanya Fluktuasi Harga Kedelai - Asti Oktaviani, Firda; Dharmawan, Budi; Darmawati Putri, Dindy (Jurnal Etnik: Ekonomi-Teknik, 2021)
Tempe is a typical Indonesian food made fermented soybeans. Tempe is a good source of nutrition because it contains protein, carbodydrates, fat, vitamins and minerals needed by the body. Soybean used to make tempe must be of good quality. Pliken Village is a tempe production center, because it has the highest number of tempe craftsmen in Banyumas Regency. With the increase in soybean prices which have continued to increase lately, the tempe business has decreased due to lack of capital to continue the business. The purpose of this research are to: 1). Knowing the amount of costs, revenues and income before and after increase in soybean prices in the tempe production business in Pliken Village. 2). Knowing the factors that affect the increase in tempe production costs. The researh was carried out in Pliken Village from May 2021 to July 2021. The target of this research is the tempe craftsmen of Pliken Village who produce for one month. The sampling method uses simple random sampling technique and obtained by respondents as many as 81 craftsmen using the slovin formula. The analytical method used is the analysisno costs and revenues, and multiple linear regression analysis. Based on the results of the analysis of costs, revenues and income shows the total cost incurred by the craftsmen before the increase in soybean prices and after the increase in soybean prices is Rp. 11,883,809 per month. Based on the classical assumption test there are factors that affect the increase in production costs such as soybean prices, family labor wages, wages for non-family workers, gasoline prices, and banana leaf prices. While the factors that do not affect the increase in production costs are the price of yeast, the price of plastic and the price of used paper.